Clinical audit of genetic testing and referral patterns for fragile X and associated conditions. Issue 6 (18th February 2016) - Cotter, Megan; Archibald, Alison D.; McClaren, Belinda J.; Burgess, Trent; Francis, David; Hills, Louise; Martyn, Melissa; Oertel, Ralph; Slater, Howard; Cohen, Jonathan; Metcalfe, Sylvia A.
Abstract : An audit was conducted of laboratory/clinical databases of genetic tests performed between January 2003 and December 2009, and for 2014, as well as referrals to the clinical service and a specialist multidisciplinary clinic, to determine genetic testing request patterns for fragile X syndrome and associated conditions and referrals for genetic counseling/multidisciplinary management in Victoria, Australia. An expanded allele (full mutation, premutation or intermediate) was found in 3.7% of tests. Pediatricians requested ∼70% of test samples, although fewer general practitioners and more obstetricians/gynecologists ordered tests in 2014. Median age at testing for individuals with a full mutation seeking a diagnosis without a fragile X family history was 4.3 years (males) and 9.4 years (females); these ages were lower when pediatricians ordered the tests (2.1 years and 6.1 years, respectively). Individuals with a premutation were generally tested at a later age (median age: males, 33.2 years; females, 36.4 years). Logistic regression showed that a family history of ID (OR 3.28 P  = 0.005, CI 1.77–5.98) was the only indication to independently increase the likelihood of a test‐positive (FM or PM) result. Following testing, ∼25% of full mutation or premutation individuals may not have attended clinical services providing genetic counseling or multidisciplinary management for these families. The apparent delay in fragile X syndrome diagnosis and lack of appropriate referrals for some may result in less than optimal management for these families. These findings suggest continued need for awareness and education of health professionals around diagnosis and familial implications of fragile X syndrome and associated conditions. © 2016 Wiley Periodicals, Inc.